Extinction Stories: Review of Bryndís Snæbjörnsdóttir and Mark Wilson, You Must Carry Me Now: The Cultural Lives of Endangered Species - Aglert, Katja; Holmberg, Tora (Humanimalia, 2016)
Bryndís Snæbjörnsdóttir and Mark Wilson. You Must Carry Me Now — The Cultural Lives of Endangered Species. Göteborg: Förlaget 284, 2015. 264 pp. £25.00 (hb).